Kakuma, Turkana : dueling struggles : Africa's forgotten peoples - Yang, Daniel Cheng, 1983- (Saint Paul, Minn. : Pangaea, 2002)
Documents the way of life of the indigenous Turkana of Kenya, an ancient pastoralist people, and the over 81,000 refugees of civil war in East Africa who have fled to Kakuma Refugee Camp on Turkana land since 1992. Includes a foreword by the Dalai Lama.
Keywords: Kakuma (Kenya : Refugee camp) -- Pictorial works; Refugees -- Sudan -- Pictorial works; Turkana (African people) -- Social conditions -- Pictorial works; Kakuma (Kenya : Refugee camp); Refugees -- Kenya; Turkana (African people); Youths' writings; Sudan -- History -- Civil War, 1983-2005 -- Refugees -- Pictorial works; Kenya -- Ethnic relations -- Pictorial works; Sudan -- History -- Civil War, 1983-2005 -- Refugees; Kenya -- Ethnic relations